Identifying areas of knowledge governance for successful projects - Ghosh, Saumyendu; Amaya, Lenis; Skibniewski, Mirosław J. (Journal of Civil Engineering and Management, 2012)
Projects undertaken in the project-based industry are characterized by multiple stakeholders, uncertainty, and complexity due to the unique nature of each project. These differences also extend to knowledge movement from one project to another. Increased knowledge creation resulting from project implementation is expected to lead to numerous benefits. These benefits encompass reusability of lessons learned, as well as knowledge of strategic, operational, organizational, and managerial aspects of the firm. By adopting a unified knowledge creation framework, firms seek tangible and intangible benefits such as cost reduction, improved productivity, enhanced efficiency, and business growth. A case study was used to identify problem areas of knowledge creation and align corporate and project objectives. Incorporating a comprehensive knowledge creation plan in the organizational memory infrastructure can be a significant stride toward improving overall project management efficiency and increasing the organization’s productivity and profitability in the industry. This stream of research will allow researchers to further refine knowledge creation success models. The paper will also draw practitioners’ attention to areas where investment is needed to improve the knowledge governance process.